Development of an Entrepreneurship Education Policy Model in the Context of Islamic Character for Students in Schools - Wartomo; Martono (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to improve the knowledge, skills, and motivation of entrepreneurship education models for students and teachers in junior high schools in Sleman Regency with the hope that after students complete their studies they can become entrepreneurs or entrepreneurs. This study consists of three variables: (1) the intensity of entrepreneurship education model services; (2) entrepreneurial skills for students in schools; (3) the effectiveness of entrepreneurship education model services in the context of national character education for students in schools. The research method used is descriptive qualitative which includes surveys, observations, interviews, questionnaires, documentation, and action research, giving assignments to research subjects and evaluation. The research location is in Sleman Regency. The sample of this study consists of two junior high schools, namely SMP Muhammadiyah 1 and SMP Muhammadiyah 2 Melati, Sleman. The research was conducted from July 2011 to November 2011. Quantitative data analysis uses a quantitative descriptive approach, while qualitative data uses an interactive approach. The results of the study show that teachers in junior high schools can follow the implementation of the entrepreneurship education model and students gain entrepreneurial skills that can make them productive business groups in their neighborhoods. Nearly 120 students are interested in participating in entrepreneurship education, thus encouraging students to become young entrepreneurs who develop according to the current digital generation.